Laboratory Examination in Hemophagocytic Lymphohistiocytosis - Wulyansari Wulyansari; Yetti Hernaningsih (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Hemophagocytic Lymphohistiocytosis (HLH) is derived from the word hemophagocytosis, in which macrophagesinfiltrate tissue extensively, and unspecifically phagocyte blood and bone marrow cells. The deviant activation of cytotoxicCD8+ T-cells causing the release of inflammatory cytokines is the core pathogenesis of HLH. Hemophagocyticlymphohistiocytosis is a regulatory disorder of the immune system, with clinical signs and symptoms of extremeinflammation and cytopenia, hepatitis, and severe and life-threatening central nervous system dysfunction. The name of theHLH disorder was recently proposed to be